Vertical Integration, Organizational Governance, and Firm Performance: Evidence from Italian Business Groups. (11th September 2014) - Cainelli, Giulio; Iacobucci, Donato
Abstract : Assuming transaction cost economics as a normative tool, we investigate the relationship between firms' 'observed' vertical integration choices and their economic performance. We use a two‐stage methodology: in the first, a measure of governance misalignment is computed as a difference between the governance form (i.e., ownership or outsourcing) predicted by transaction cost economics and the form actually observed; the second stage consists of estimating a performance equation where the misalignment variable is introduced together with a set of independent variables. Compared with previous studies, we introduce two novelties: we use the business group as the unit of analysis to detect the ownership of vertically related productions; we assess the moderating role of geographic agglomeration in reducing the need of vertical integration. Our results confirm the importance of technology and price uncertainty in influencing vertical integration; moreover, the misalignment variable is significant in the case of profitability, but not in the case of growth. Copyright © 2014 John Wiley & Sons, Ltd.